2018
DOI: 10.3390/w10060731
|View full text |Cite
|
Sign up to set email alerts
|

What Germany’s University Beginners Think about Water Reuse

Abstract: Water reuse is a new technology, not yet implemented, but discussed for use in Germany. Public opinion plays a major role in the success of the introduction of this new technology and was not yet analyzed for Germany. When monitoring 340 university beginners' conceptions regarding water reuse, a variety of conceptions appeared. While usage of tap water is accepted for drinking purposes, acceptance of recycled water for oral consumption was low. When asked for reasons for (not) using recycled water, three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Hence, those gaps are subject areas that need to be explained in very basic terms to prevent students from explaining these concepts based on their own experiences, leading to superficial approaches and interpretations that differ from scientific perspectives. Schmid’s & Bogner’s [ 94 ] study on students’ conceptions on water reuse supports this claim. Although knowledge about new technologies of water reuse was missing, students expressed concern about water quality.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hence, those gaps are subject areas that need to be explained in very basic terms to prevent students from explaining these concepts based on their own experiences, leading to superficial approaches and interpretations that differ from scientific perspectives. Schmid’s & Bogner’s [ 94 ] study on students’ conceptions on water reuse supports this claim. Although knowledge about new technologies of water reuse was missing, students expressed concern about water quality.…”
Section: Discussionmentioning
confidence: 89%
“…Although knowledge about new technologies of water reuse was missing, students expressed concern about water quality. Schmid & Bogner [ 94 ] concluded well-thought outreach activities as necessary to create acceptance. Alternative or missing conceptions on special topics are essential clues for educators and experts in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, public perception was reported to be one of the main problems preventing successful application of water reuse projects [18]. On the other hand, it was found that university students in Germany generally have positive attitudes towards water reuse, but at the same time they had many doubts about its quality [19].…”
Section: Introductionmentioning
confidence: 99%
“…Showering and drinking water received the least acceptance. The perceived health risk was judged to be a determining factor, and higher educational level contributed to a greater likelihood of acceptance [63]. In addition, knowledge of possible unplanned reuse led to a higher level of acceptance of planned reuse.…”
Section: Social Acceptance In Europe Regarding the Reuse Of Treated W...mentioning
confidence: 99%
“…Students in Germany who had no previous experience with reuse systems showed acceptance especially for applications such as watering plants and the garden, flushing the toilet, or washing the car [63]. Showering and drinking water received the least acceptance.…”
Section: Social Acceptance In Europe Regarding the Reuse Of Treated W...mentioning
confidence: 99%